2018
DOI: 10.1104/pp.17.01679
|View full text |Cite
|
Sign up to set email alerts
|

Foxtail mosaic virus: A Viral Vector for Protein Expression in Cereals

Abstract: Rapid and cost-effective virus-derived transient expression systems for plants are invaluable in elucidating gene function and are particularly useful in plant species for which transformation-based methods are unavailable or are too time and labor demanding, such as wheat () and maize (). The virus-mediated overexpression (VOX) vectors based on and described previously for these species are incapable of expressing free recombinant proteins of more than 150 to 250 amino acids, are not suited for high-throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 52 publications
1
112
0
Order By: Relevance
“…The use of virus‐induced gene silencing (VIGS) in wheat and other cereals has been highly successful in characterizing the impact of various genes involved in abiotic and biotic stress response (Cakir et al ., ; Ramegowda et al ., ; Lee et al ., ). These VIGS systems are now well established for use in wheat, and more recently advances in virus‐mediated overexpression have demonstrated the feasibility of their use in wheat for both small and large proteins (Bouton et al ., ; Cheuk and Houde, ). Beyond viral expression systems, other possibilities for transient expression in wheat exist.…”
Section: Gene Validation In Polyploid Wheatmentioning
confidence: 99%
“…The use of virus‐induced gene silencing (VIGS) in wheat and other cereals has been highly successful in characterizing the impact of various genes involved in abiotic and biotic stress response (Cakir et al ., ; Ramegowda et al ., ; Lee et al ., ). These VIGS systems are now well established for use in wheat, and more recently advances in virus‐mediated overexpression have demonstrated the feasibility of their use in wheat for both small and large proteins (Bouton et al ., ; Cheuk and Houde, ). Beyond viral expression systems, other possibilities for transient expression in wheat exist.…”
Section: Gene Validation In Polyploid Wheatmentioning
confidence: 99%
“…Current chemical DNA synthesis prices are not compatible with routine cloning, although a sharp price drop catalysed by new technology developments is expected in the near future (Schindler et al, 2018). In the plant virology field, infectious clones have been reported for delivery of tobamovirus, tombusvirus and potexvirus genomes synthesized entirely from scratch (Bouton et al, 2018;Cooper, 2014;Lovato et al, 2014). Due to errors in the reference sequence used, a first version of the synthetic tobamovirus genome was not infectious.…”
Section: From Clone Assembly To De Novo Synthesismentioning
confidence: 99%
“…Inverted‐repeats carried at this position were most efficient at inducing VIGS (Liu et al, ). Bouton et al () also duplicated the CP promoter and demonstrated that FoMV could be used to transiently express marker and fungal effector proteins from this position in N. benthamiana , wheat, and maize. Disarmed FoMV vectors for transient gene expression have also been developed by substitution of the TGB or CP with genes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The development of viral vectors for monocot plants has been emerging rapidly in recent years (Lee, Hammond-Kosack, & Kanyuka, 2015). To date, at least eight different viruses have been developed into viral vectors for monocots, including barley stripe mosaic virus (BSMV) (Lee, Hammond-Kosack, & Kanyuka, 2012;Scofield, Huang, Brandt, & Gill, 2005), brome mosaic virus (BMV) (Ding, Schneider, Chaluvadi, Mian, & Nelson, 2006), cymbidium mosaic virus (CymMV) (Hsieh et al, 2013), rice tungro bacilliform virus (RTBV) (Purkayastha, Mathur, Verma, Sharma, & Dasgupta, 2010), wheat streak mosaic virus (WSMV) (Choi, Stenger, Morris, & French, 2000;Tatineni, McMechan, Hein, & French, 2011), bamboo mosaic virus (BaMV) together with its associated satellite RNA (Liou, Huang, Hu, Lin, & Hsu, 2014), cucumber mosaic virus (CMV) (Wang et al, 2016), barley yellow striate mosaic virus (BYSMV) (Gao et al, 2019), and foxtail mosaic virus (FoMV) (Bouton et al, 2018;Liu et al, 2016;Mei & Whitham, 2018;Mei, Zhang, Kernodle, Hill, & Whitham, 2016). Seven of the virus vectors are designed for VIGS applications (BSMV, BMV, CymMV, RTBV, BaMV, CMV, and FoMV), and four can be used for systemic gene expression (BSMV, BYSMV, FoMV, and WSMV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation